2006
DOI: 10.1017/s0012162206000314
|View full text |Cite
|
Sign up to set email alerts
|

Predicting additional care in young children with neurodevelopmental disability: a systematic literature review

Abstract: Children with developmental disabilities often show a variety of associated impairments that lead to a lifelong need for additional care. Careful assessment of these impairments is required not only for diagnostic purposes but also to inform the parents about the expected additional care needs in the future. We present a systematic review of the literature to identify instruments that classify the type and amount of this care for the individual child. A literature search was performed in the Medline database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…Numerous outcome instruments are available that measure impairment in body structure and function, ability in daily activities, and participation (Majnemer 2006). Some measurement tools that capture the impact on caregivers are also available (Mackie et al 2002;Meester-Delver et al 2006;Narayanan et al 2006), as well as the amount of caregiver assistance and equipment required in daily self-care, mobility and social function (Haley et al 1992). However, a brief measurement tool that provides an indication of the amount of assistance that schoolaged children with disabilities require to participate in leisure, play and recreational pursuits, from the primary carer's perspective, is not available.…”
mentioning
confidence: 99%
“…Numerous outcome instruments are available that measure impairment in body structure and function, ability in daily activities, and participation (Majnemer 2006). Some measurement tools that capture the impact on caregivers are also available (Mackie et al 2002;Meester-Delver et al 2006;Narayanan et al 2006), as well as the amount of caregiver assistance and equipment required in daily self-care, mobility and social function (Haley et al 1992). However, a brief measurement tool that provides an indication of the amount of assistance that schoolaged children with disabilities require to participate in leisure, play and recreational pursuits, from the primary carer's perspective, is not available.…”
mentioning
confidence: 99%
“…This information helps parents to plan individual care, physicians to deliver adequate and timely medical interventions, and service providers to make optimal decisions about resource policies and quality assurance 2,3 . However, a systematic review revealed that suitable instruments to classify the consequences of developmental disabilities in young children, in terms of future dependence on additional care, were not available 4 …”
mentioning
confidence: 99%
“…2,3 However, a systematic review revealed that suitable instruments to classify the consequences of developmental disabilities in young children, in terms of future dependence on additional care, were not available. 4 The Capacity Profile (CAP) has been developed based on clinical experience in the field of paediatric rehabilitation. 5 The CAP classifies additional care (Appendix I) and fits into the framework of the International Classification of Functioning, Disability and Health (ICF), 6 of: (1) body functions and body structures, (2) activities and participation, and (3) contextual (e.g.…”
mentioning
confidence: 99%
“…A previous literature search showed a lack of available instruments to obtain such information. 10 In the development of the CAP, the ICF classification was the frame of reference. 7 The ICF lists environmental factors that interact with body functions, activities, and aspects of participation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 To our knowledge, there is still no rating scale that classifies comprehensively the functional outcome in terms of dependency on additional care of children with developmental disabilities. 10 This motivated us to develop the Capacity Profile (CAP): a standardized method to classify the needs of children for additional care indicated by their various impairments.…”
mentioning
confidence: 99%